2023
DOI: 10.1038/s41419-023-06171-7
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/mTOR inhibitors promote G6PD autophagic degradation and exacerbate oxidative stress damage to radiosensitize small cell lung cancer

Huan Deng,
Yamei Chen,
Li Wang
et al.

Abstract: Our previous study revealed that PI3K/AKT/mTOR signaling was associated with SCLC radioresistance. SBC2 cells were used as primary radioresistance models, while H446 cells were continuously exposed to ionizing radiation (IR) to develop acquired radioresistance. Cell viability and apoptosis assays were used to investigate synergistic effects of BEZ235/GSK2126458 and IR in vitro, while immunoblotting, metabolite quantitative analysis and bioinformatic analyses were utilized to explore the underlying mechanism. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Using mass spectrometry analysis, we found that the mTOR signaling pathway was activated in the hypophysectomized rats, associated with disturbed lipid homeostasis and oxidative stress. Although there is no clear evidence linking mTOR signals to NADPH regeneration, several studies have shown that mTOR inhibitors can promote G6PD autophagy degradation and exacerbate oxidative stress damage ( 61 ); modulate IDH2 expression ( 62 ). As mTOR’s role in metabolism is context-dependent and integrates various signals, including nutrient availability, growth factors and energy status, its effects on fatty acid oxidation and NADPH regeneration are probably mediated by complex networks of direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using mass spectrometry analysis, we found that the mTOR signaling pathway was activated in the hypophysectomized rats, associated with disturbed lipid homeostasis and oxidative stress. Although there is no clear evidence linking mTOR signals to NADPH regeneration, several studies have shown that mTOR inhibitors can promote G6PD autophagy degradation and exacerbate oxidative stress damage ( 61 ); modulate IDH2 expression ( 62 ). As mTOR’s role in metabolism is context-dependent and integrates various signals, including nutrient availability, growth factors and energy status, its effects on fatty acid oxidation and NADPH regeneration are probably mediated by complex networks of direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy regulates glycolysis via selective degradation of HK2 [ 26 ]. Additionally, G6PD is degraded by chaperone-mediated autophagy processes [ 27 ]. However, whether DCBLD1 activates autophagy to degrade G6PD, leading to metabolic reprogramming needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This oxidative environment promotes the oxidation of macromolecules, including DNA, leading to consequential DNA damage. Glycolysis plays a crucial role in sustaining rapid DNA repair and alleviating oxidative stress by regulating the pentose phosphate pathway in lung cancer (6,7). Metabolic rewiring, coupled with the action of antioxidant defense enzymes such as glutathione peroxidase 4 (GPX4), enables cancer cells tolerate treatment by improving their redox capacity and developing adaptive mechanisms to counteract oxidative stress.…”
Section: Introductionmentioning
confidence: 99%